Examining the effect of real-time visual feedback on the quality of rowing technique - Fothergill, S. (Procedia Engineering, 2010)
An application is presented that provides real-time visual feedback on technique to a rower using an ergometer. The effects of using this system to support professional coaches in a genuine training scenario are investigated. This evaluation claims the system is a suitable training tool for helping to maintain consistently good technique.